Validation of the Wilks powerlifting formula - Vanderburgh, P. M.; Batterham, A. M. (Medicine & Science in Sports & Exercise, 1999)
Purpose: Because maximal strength varies with body mass, the International Powerlifting Federation (IPF) has adopted a method of adjusting powerlifting events (bench press, BP; squat, SQ; deadlift, DL, and total lift (the sum of BP, DL, and SQ), TOT) by body mass. This method, the Wilks formula, multiplies one's lift by an index based on body mass so that lifters of different size can be compared on the same event. The Wilks formula is not, however, based on published data and has yet to be critically evaluated. The purpose of this investigation, then, was to validate the Wilks formula. Methods: This was performed by 1) examining residuals bias to verify that the adjusted score does, in fact, lead to no systematic bias based on body mass and 2) by applying a more theoretically supportable allometric model to the same data and comparing the fit with the Wilks approach. Subjects were the current men's and women's world record holders as well as the top two performers for each event in the IPF's 1996 and 1997 World Championships (a total of 30 men and 27 women for each lift). Results: Results of data analysis regarding the Wilks formula indicate that: 1) there is no bias for men's or women's BP and TOT; 2) there is a favorable bias toward intermediate weight class lifters in the women's SQ with no bias for men's SQ; and 3) there is a linear unfavorable bias toward heavier men and women in the DL. Furthermore, the allometric approach indicated a bias against light and heavy men and women which may be considered acceptable given that half as many lifters are found in the lightest and heaviest weight classes as in the intermediate weight classes. Conclusion: As used currently (BP and TOT only), the Wilks formula appears to be a valid method to adjust powerlifting scores by body mass.